Trends of laparoscopic gynecologic surgeries in a tertiary care center: A five-year retrospective study - Ghimire, Asmita; Pant, Padam Raj; Subedi, Nilam; Pant, Samriddha Raj (Grande Medical Journal, 2019)
Background: The use of laparoscopic surgery in modern gynecology has led to faster recovery, lesser hospital stay, and fewer complications. In this study, we aim to analyze the current trends in laparoscopic surgery, its indications, type of procedure and associated complications.Method: This is a retrospective study done in Grande International Hospital. All patients who underwent laparoscopic surgery over a duration of 5 years from July 2013 to June 2018 were analyzed.Result: There were a total of 419 laparoscopic surgeries (74 diagnostic, 345 therapeutic) performed. The most common age group of patients for diagnostic laparoscopy was 25-34 years and for therapeutic was 45-54 years. Therapeutic surgery was mostly performed for ovarian cyst (144, 41.74%). There were a total of 152 (44.06%) laparoscopic hysterectomies performed. Complications which occurred during the surgery were insignificant (p